Classical Discourses of Liberation: Shared Botanical Metaphors in Sarvastivada Buddhism and the Yoga of Patañjali - O'Brien-Kop, Karen (Religions of South Asia, 2018)
Conventionally, the label 'classical yoga' has been aligned with-and sometimes conflated with-the text of Patañjali's Yogasutra. Yet if we broaden the scope of inspection to a wider textual corpus, we can identify a richer and more complex discourse of classical yoga in soteriological contexts. This discourse is also employed in Buddhist Sarvastivada traditions and is semantically and metaphorically entangled across religious boundaries. By comparing passages from the Patañjalayogasastra and the Abhidharmakosabhasya, this article highlights the botanical image of the seed and its seedbed (the substratum) as a key metaphorical structure in the soteriology of the two texts.